Pengaruh Tingkat Kualitas Pelayanan Terhadap Kepuasan Nasabah Dengan Metode Index Potential Gain Customer Value (PGCV) - Cindy Sekar Arum; Sri Ramadhani; Muhammad Ikhsan Harahap (Faculty of Islamic Religion, Universitas Muhammadiyah Sumatera Utara, 2023)
This study aims to see and analyze the effect of service quality on customer satisfaction at PT. Bank SUMUT KCP Sharia Trading in Simalungun Regency using the Index Potential Gain Customer Value method. The research method used in this study is the PGCV method. In addition to supporting this method, a quantitative approach is also used in this study to strengthen the research results. The sample used was 100 people, with a Likert scale-based questionnaire for data collection. Based on the results of the tests conducted, it is said that service quality has a significant effect on customer satisfaction as evidenced by t count 10.578 t table 1.984 with a significance value of 0.000 0.05. As well as with the help of Cartesian diagrams the customer's top priority, namely quadrants I and II which are considered influential for the customer. Quadrant I includes (R2, R3, R5, T3, E3) services must be improved to support customer satisfaction at PT. Bank Sumut Trade Sharia KCP Simalungun Regency.